2014
DOI: 10.5194/bgd-11-15889-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental factors controlling lake diatom communities: a meta-analysis of published data

Abstract: Introduction Conclusions References Tables Figures Back Close Full Screen / Esc Printer-friendly Version Interactive Discussion Abstract Introduction Conclusions References Tables Figures Back Close Full Screen / Esc Printer-friendly Version Interactive Discussion AbstractDiatoms play a key role in the development of quantitative methods for environmental reconstruction in lake ecosystems. Diatom-based calibration datasets developed during the last decades allow the inference of past limnological variables suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Diatom literature 50,51 stresses the importance of ion concentration and trophic status as major environmental drivers of diatom distributions in lakes and streams, 52 while physical factors typically have a lesser effect on community structure. Moreover, studies where spatial configuration accounted for a significant proportion of the community variance clearly outnumbered the studies suggesting strict local environmental control.…”
Section: Advanced Review Wireswileycom/watermentioning
confidence: 99%
“…Diatom literature 50,51 stresses the importance of ion concentration and trophic status as major environmental drivers of diatom distributions in lakes and streams, 52 while physical factors typically have a lesser effect on community structure. Moreover, studies where spatial configuration accounted for a significant proportion of the community variance clearly outnumbered the studies suggesting strict local environmental control.…”
Section: Advanced Review Wireswileycom/watermentioning
confidence: 99%
“…A comparison of the paleorecords from Lac Brûlé and Lac Noir (25 km apart) showed that the vegetation surrounding each of the two sites responded to environmental changes similarly in timing and direction of change, with some exceptions (Lafontaine-Boyer and Gajewski, 2014). Diatom community composition was more unique to each lake as a result of local catchment-scale characteristics, including basin morphometry, habitat availability, water chemistry, and disturbances (Blanco, 2014). Regardless, most of the pollen taxa and several of the abundant diatom species were common to both sites and were directly comparable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are distributed throughout the world in nearly all types of aquatic systems and are one of the most important food resources in marine and freshwater ecosystems [Wichard et al, 2007;Medlin 2011]. A key issue in understanding diatom distribution is knowing the extent to which they are constrained by geographical factors that limit species dispersal vs. the extent to which they are limited only by the ability of the species to grow under a specific combination of environmental factors [Blanco 2014]. Ability of populations to compete and persist in a new local habitat depends on how well adapted they are to grow under its environmental conditions.…”
Section: Introductionmentioning
confidence: 99%